1983
DOI: 10.1002/pol.1983.170210515
|View full text |Cite
|
Sign up to set email alerts
|

Backbone‐assisted reactions of polymers. V. Kinetics of isomerization of poly(chloromethylthiirane) and poly(3‐chlorothietane) in solution

Abstract: The reversible isomerization of poly(chloromethylthiirane) and poly(3‐chlorothietane) represents a new kind of polymer reaction and a new method of copolymer synthesis. In chloroform, in dichloromethane, or in nitrobenzene the reaction is well described by reversible first‐order kinetics. A rate increase of ca. 40% on changing the solvent from chloroform to nitrobenzene is consistent with an isomerization mechanism that involves a rate‐determining attack of the backbone sulfur atom on the neighboring carbon‐ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Therefore, the processes (steps 3 and 4) were carried out under the protection of nitrogen, and mercaptans were filtered quickly at low temperature (cooled with an ice‐bath and washed using ice‐water). Second, it has been reported that PCMT is rather unstable as regards its isomerization 21, 22. The subsequent reaction to yield copolymers, therefore, must be carried out at an appropriate time after formation of PCMT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the processes (steps 3 and 4) were carried out under the protection of nitrogen, and mercaptans were filtered quickly at low temperature (cooled with an ice‐bath and washed using ice‐water). Second, it has been reported that PCMT is rather unstable as regards its isomerization 21, 22. The subsequent reaction to yield copolymers, therefore, must be carried out at an appropriate time after formation of PCMT.…”
Section: Resultsmentioning
confidence: 99%
“…PCMT has not been used for the preparation of linear copolymers because of its complicated structure resulting from an unusual rearrangement at room temperature. Zussman and Tirrell proposed a likely mechanism for its isomerization, as shown in Scheme 21, 22. It was believed that the existing main form of PCMT were structures (a) and (b) for the fresh polymer and structure (c) appeared after three months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, poly (styrene‐alt‐maleic acid) has been synthesized and shown to be coordinated with metals through two carboxylic groups pertaining to two different polymer chains which indicate intermolecular complexation. Moreover, chelating resins with sulfur and nitrogen as donor atoms usually have excellent adsorption properties for mercury and noble metal ions …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chelating resins with sulfur and nitrogen as donor atoms usually have excellent adsorption properties for mercury and noble metal ions. [18,19] In this work, a new type of reactive copolymer has been synthesized by the modification of a linear copolymer of Poly (styrene-alt-maleic anhydride) by 3-aminobenzoic acid. The prepared resin has a good potential for crosslinking by 1, 2-diaminoethane and 1, 3-diaminopropane for the preparation of porous resin beads.…”
Section: Introductionmentioning
confidence: 99%